PENGARUH INFLUENCER, SOCIAL MEDIA CONTENT, DAN E-WOM TERHADAP VISITORS DECISION DENGAN VISITORS INTEREST SEBAGAI VARIABEL MEDIASI : STUDI KASUS ASIA FARM DAN ASIA HERITAGE - Umairoh, Dini; N, Arizal; Nofrizal, Nofrizal; Lukcyhasnita, Andam (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The digital revolution has fundamentally transformed the landscape of tourism marketing, where travel decisions are now heavily influenced by visual and social representations in online media. This study aims to analyze the influence of influencers, social media content, and electronic word of mouth (e-WOM) on visitors' decisions, with visitors' interest serving as a mediating variable. Using a quantitative explanatory approach, data were collected through an online survey of 350 respondents who had visited the Asia Farm and Asia Heritage tourist destinations in Pekanbaru City. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results of the study indicate that influencers, social media content, and e-WOM have a positive and significant effect on visitors' interest. Furthermore, it was found that visitors' interest plays a significant role as a mediator in bridging digital stimuli to the final decision of tourists to visit. Influencers were found to have the most dominant influence in shaping interest, while aesthetic visual content on platforms such as TikTok and Instagram strengthens visit intentions. These findings underscore the importance of digital marketing strategies based on credibility and emotional engagement for managers of educational tourism destinations in the modern era. Keywords: Influencer, Visitors interest , Visitors Decision, Digital Tourism. Abstrak: Revolusi digital telah mengubah lanskap pemasaran pariwisata, di mana keputusan berkunjung kini sangat dipengaruhi oleh representasi visual dan sosial di media daring. Penelitian ini bertujuan untuk menganalisis pengaruh influencer, social media content, dan electronic word of mouth (e-WOM) terhadap visitors decision dengan visitors interest sebagai variabel mediasi. Menggunakan pendekatan kuantitatif eksplanatori, data dikumpulkan melalui survei daring terhadap 350 responden yang merupakan pengunjung destinasi wisata Asia Farm dan Asia Heritage di Kota Pekanbaru. Analisis data dilakukan menggunakan Structural Equation Modeling (SEM) berbasis Partial Least Squares (PLS) dengan perangkat lunak SmartPLS. Hasil penelitian menunjukkan bahwa influencer, social media content, dan e-WOM berpengaruh positif dan signifikan terhadap visitors interest . Lebih lanjut, ditemukan bahwa visitors interest berperan sebagai mediator yang signifikan dalam menjembatani stimulus digital terhadap keputusan akhir wisatawan untuk berkunjung. Influencer ditemukan memiliki pengaruh paling dominan dalam membentuk minat, sementara konten visual yang estetik di platform seperti TikTok dan Instagram memperkuat niat kunjungan. Temuan ini menegaskan pentingnya strategi pemasaran digital yang berbasis pada kredibilitas dan keterlibatan emosional bagi pengelola destinasi wisata edukatif di era modern. Kata kunci: Influencer, Visitors interest , Visitors Decision, Digital Tourism.